An electrical- and chemical-free approach using microfilter and Ag-based catalysts for emergency drinking water treatment - Thuy, Nguyen Thi (Environmental technology, 2024)
In emergency cases such as disasters, supplying enough safe drinking water is one of the most urgent needs for human life. This research aimed to develop a chemical- and electricity-free drinking water treatment system based on microfiltration and catalysts of Ag and Ag-TiO2-SiO2 coated on glass spheres in both dark and sunlight conditions. The system was applied to treat raw water samples taken from five rivers in Vietnam, simulated floodwater samples with high turbidity and E. coli concentration, and real flooding water samples. The results showed the filtration unit fed with simulated floodwater generated lower fluxes and shorter working durations before chemical cleaning than that fed with normal river water. However, filtrate quality was not significantly different for these five water samples with very low values of turbidity (0-0.66 NTU), total coliform (5-19 CFU (100 mL)-1), and E. coli (0-17 CFU (100 mL)-1). The catalyst units using glass spheres coated with either Ag in dark and sunlight or Ag-TiO2-SiO2 under sunlight can completely remove E. coli and coliform as well as additionally mitigate natural organic matters. This study hence suggests the combination of microfiltration and Ag-based catalytic treatment for safe drinking water supply in emergencies, especially for flooding conditions